Does Individual Performance Mediate the Effect of Organizational Commitment on Job Satisfaction of Village Government Apparatus? - Irfandi Buamonabot; Muhammad Asril Arilaha; Suratno Amiro (CV. Media Digital Publikasi Indonesia, 2026)
The purpose of this study was to examine the role of individual performance in mediating the relationship between organizational commitment and job satisfaction among village government employees in West Halmahera Regency, North Maluku Province. Using a hierarchical regression methodological approach, the prerequisites for direct effects between organizational commitment, individual performance, and job satisfaction were simultaneously tested. The sample in this study consisted of 133 respondents consisting of village heads, village secretaries, and heads of divisions (finance, general affairs, and planning) selected using a questionnaire survey method. Data were analyzed using validity and reliability tests, as well as simple linear and hierarchical regression. The results showed that all tests of direct relationships as prerequisites for mediation were successfully empirically supported. Furthermore, the main contribution of this study is proving that individual performance significantly acts as a mediating variable in the relationship between organizational commitment and employee job satisfaction. This finding emphasizes the importance of managing village apparatus performance in order to translate organizational commitment into optimal job satisfaction.